2019
DOI: 10.3390/genes10020172
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Human DNA Methyltransferases and Their Isoforms in Shaping the Epigenome

Abstract: A DNA sequence is the hard copy of the human genome and it is a driving force in determining the physiological processes in an organism. Concurrently, the chemical modification of the genome and its related histone proteins is dynamically involved in regulating physiological processes and diseases, which overall constitutes the epigenome network. Among the various forms of epigenetic modifications, DNA methylation at the C-5 position of cytosine in the cytosine–guanine (CpG) dinucleotide is one of the most wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 152 publications
(217 reference statements)
1
108
0
2
Order By: Relevance
“…5n). Moreover, although DNMT1 has generally been thought to be responsible for maintenance of DNA methylation during cell division, it is increasingly evident that rather than being restricted to de novo imprinting roles during development, DNMT3 is an important contributor to the maintenance of the DNA methylome landscape 55 . Of relevance therefore, parallel mRNA expression analysis showed that whilst rewiring of SFs from CIA mice was reflected by reduced levels of DNMT1 but not DNMT3, the more pronounced remodelling of the methylome seen with CIA-ES-62 SFs was associated with downregulation of both DNMT1 and DNMT3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5n). Moreover, although DNMT1 has generally been thought to be responsible for maintenance of DNA methylation during cell division, it is increasingly evident that rather than being restricted to de novo imprinting roles during development, DNMT3 is an important contributor to the maintenance of the DNA methylome landscape 55 . Of relevance therefore, parallel mRNA expression analysis showed that whilst rewiring of SFs from CIA mice was reflected by reduced levels of DNMT1 but not DNMT3, the more pronounced remodelling of the methylome seen with CIA-ES-62 SFs was associated with downregulation of both DNMT1 and DNMT3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CGI is mostly found in gene promoter regions in which DNA methylation can modify gene expression by regulating the recruitment of methylated DNA-binding proteins or by changes in the accessibility of the DNA sites, which influence transcription factor binding and overall chromatin structure [53,54]. Commonly, DNA methylation of the promoter regions is generally associated with gene silencing, although this rule is not valid for promoters with low CpG density [55]. Furthermore, the methylation status of enhancers exhibiting widespread hypo-methylation during development [56], and for which interactions with promoters could be blocked by insulators, is also key to controlling gene expression in development and cell function [51,57].…”
Section: Dna Methylationmentioning
confidence: 99%
“…DNMTs are classified into three categories, DNMT1, DNMT2, DNMT3 [DNMT3a, DNMT3b, and DNMT3L] (Lyko, 2018;Gujar et al, 2019). DNMT1 is involved in the maintenance methylation (Ren et al, 2018).…”
Section: Dna Methyltransferases (Dnmts)mentioning
confidence: 99%